(untitled) (World Bulletin of Social Sciences, 2023)
Understanding politeness is cited in the monograph of N. I. Formanovskaya, as well as T. V. Larina. Thus, T. V. Larina writes: "politeness is understood as a nationally specific communicative category, the content of which is communicative behavior (linguistic and non-linguistic) aimed at compliance with socially accepted norms in harmonious, conflict-free communication and interactive communication system of ritualized strategies (establishing, maintaining and ending interpersonal communication)".